CHECKING OF THE OPERATION A DIGITAL-BASED FAULT SIRIUS-2-DPD USING MEASUREMENT SOFTWARE AND HARDWARE COMPLEXSET OMICRON CMC 356 - Svyatoslav Strakhov; Dmitry Oleynikov; Pavel Vivchar; Sergey Jastrebov; Roman Bashmakov; Victoria Lykhmanova (Вестник Северо-Кавказского федерального университета, 2022)
This article considers the possibility of checking «Sirius-2-DPD» multipurpose microprocessor terminal using the measurement software and hardware complex Omicron CMC 356. Take a virtual model of the electrical network, made up of its equivalent circuit, rated currents and voltages are normal and emergency modes at different points of the equivalent circuit, set the document to check the function of weapons ofmass destruction device «Sirius-2-DPD» on the basis of the software «Omicron CMC 356». Check of the accuracy of the definition places damage function as a part of the device «Sirius-2-DPD». Determine the distance error indications to fault when the two-phase and three-phase short circuit.